Strategi Koping Terhadap Kepatuhan Minum Obat pada Pasien TB Paru - Yuly Abdi Zainurridha; Tintin Sukartini; Harmayetty Harmayetty (FORIKES, 2020)
Most tuberculosis germs attack the lungs, but can also affect other organs. Factors that allow a person exposed to tuberculosis bacteria are the concentration of sparks in the air and the length of time inhaled the air. The purpose of this study is to describe coping strategies for adherence to taking medication from pulmonary TB patients. This type of research was descriptive. The study population was all pulmonary TB patients in RSUD dr. Abdoer Rahem Situbondo from May to June 2019, with a population size of 102 people. The sample size was 100 patients selected by purposive sampling technique. Data was collected through filling out questionnaires and focus group discussions, then analyzed descriptively. In general, the results of the study indicate that coping potential and future expectations are high, social support obtained by TB patients is good, and their coping strategy is effective. Keywords: tuberculosis; taking medication; coping strategies; adherence